2012
DOI: 10.1371/journal.pone.0048452
|View full text |Cite
|
Sign up to set email alerts
|

NT-ProBNP Levels in Saliva and Its Clinical Relevance to Heart Failure

Abstract: BackgroundCurrent blood based diagnostic assays to detect heart failure (HF) have large intra-individual and inter-individual variations which have made it difficult to determine whether the changes in the analyte levels reflect an actual change in disease activity. Human saliva mirrors the body’s health and well being and ∼20% of proteins that are present in blood are also found in saliva. Saliva has numerous advantages over blood as a diagnostic fluid which allows for a non-invasive, simple, and safe sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 34 publications
0
63
0
Order By: Relevance
“…Therefore, if researchers use saliva to measure BNP and IL-10, they can expect that salivary results will be lower than serum results and that salivary values may underestimate high serum values. Foo et al (2012) reported that salivary NT-proBNP was 100% specific inidentifying patients with HF in comparison to healthy controls. Our study differed from Foo's in that we did not have healthy controls in our study, we measured BNP rather than NT-proBNP, and we used the Bland-Altman test in addition to correlation testing.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, if researchers use saliva to measure BNP and IL-10, they can expect that salivary results will be lower than serum results and that salivary values may underestimate high serum values. Foo et al (2012) reported that salivary NT-proBNP was 100% specific inidentifying patients with HF in comparison to healthy controls. Our study differed from Foo's in that we did not have healthy controls in our study, we measured BNP rather than NT-proBNP, and we used the Bland-Altman test in addition to correlation testing.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, monoclonal antibodies that target the nonglycosylated sites between NTproBNP 28 -45 [i.e., NT-proBNP 30 -35 (Glu-Leu-GlnVal-Glu-Gln motif)] are likely to exclude the effects of O-glycosylation on the measurement of plasma NTproBNP. This, together with monoclonal antibodies targeting NT-proBNP [13][14][15][16][17][18][19][20] , is likely to provide a more standardized measurement of the plasma NT-proBNP for future "sandwich" immunoassays. Our data indicated that although immunoreactive NT-proBNP was present in human plasma as multiple fragments of the full-length NT-proBNP molecule, specific epitopes of the peptide appear to be more abundant, providing ideal targets for developing the next generation diagnostic assays for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…The 6 NT-proBNP immunoassays are named according to the first amino acid that the capture antibody binds to on the NT-proBNP molecule and the last amino acid that the detection antibody binds to on the NT-proBNP molecule of 1-76 amino acids: NT-proBNP 1-20 (5B6 1-12 and 13G12 [13][14][15][16][17][18][19][20] ); NT-proBNP (18H5 [13][14][15][16][17][18][19][20] and 11D1 28 -45 ); NTproBNP (5B6 [1][2][3][4][5][6][7][8][9][10][11][12] and 11D1 28 -45 ); NT-proBNP 28 -76 (11D1 28 -45 and 28F8 67-76 ); NT-proBNP (18H5 [13][14][15][16][17][18][19][20] and 28F8 67-76 ); NTproBNP 1-76 (5B6 [1][2][3][4][5][6][7][8][9][10][11][12] and 28F8 67-76 ). Each NTpr...…”
Section: Plasma Nt-probnp Alphalisa Immunoassaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, saliva samples were collected from healthy controls (n = 40) without underlying heart conditions, and from HF patients (n = 45). They demonstrated that the salivary NT-proBNP immunoassay has a clinical sensitivity of 82.2% and specificity of 100%, PPV of 100%, and NPV of 83.3%, with an overall diagnostic accuracy of 90.6% [11]. Another study revealed that higher daily salivary alpha-amylase activity output correlated with increasing levels of NT-proBNP.…”
Section: Discussionmentioning
confidence: 98%